MENGGAGAS KERANGKA KERJA MANAJEMEN HUMAS DALAM TINJAUAN AKSIOLOGI PADA LEMBAGA PENDIDIKAN - Hidayat, Ahmad Syarifi (JURNAL AL-TANZIM, 2019)
This research presents a public relations management framework in axiology review in educational institutions, where the framework has an important role in building and enhancing cooperation between schools and stake holders, guardians of students, government and other institutions to meet the needs of the institution.  This research uses a qualitative with library research. The results showed that the implementation of public relations management functions, such as planning, organizing, actuating, and evaluating will be achieved when accompanied by optimal performance of public relations practitioners. But it is not enough on the performance of an individual, public relations management in axiology review applied in schools must apply the code of conduct, the code of profession, the code of publication, the code of enterprise. To be able to implement this, it is expected that professionals in the public relations field have the ability qualifications, namely; ethical sensibility, ethical reasoning, ethical conduct, and ethical leadership.